Exploring Barriers to Academic Staff Promotion: Insights from Tanzania Higher Learning Institutions - Joyce Nemes (International Journal of Qualitative Research, 2026)
Climbing the academic ladder poses substantial challenges for many of the academicians in the Tanzanian higher learning institutions. Yet, research on promotion barriers remains scarce. Using Bourdieu’s Capital Theory, this qualitative case study aims to explore the barriers that impede academic staff promotion in Tanzanian higher learning institutions. Using purposive sampling, data were collected via in-depth interviews, document reviews, and observations. The findings show multiple, interlocking constraints. Heavy teaching and postgraduate supervision drain time capital and reduce research productivity and networking. Resource shortages and poor infrastructure reflect limited economic capital and restrict access to research tools and support. Lengthy, opaque promotion procedures and repeated re review of work already published in reputable journals undermine symbolic capital. Low intrinsic motivation points to gaps in embodied cultural capital and a misaligned habitus. Through Bourdieu’s lens, these dynamics block the conversion of time and funds into publications, recognition, and collaborative networks, hindering staff advancement. Policy recommendations: protect dedicated research time; allocate research funds more equitably; upgrade physical and digital infrastructure; accept publications from preapproved reputable journals without redundant re review. Future research should quantify these effects across more institutions and examine staff perceptions of repeated re review and its impact on morale, timelines, and career progression.